Does improving basic public health services promote household consumption of rural migrant workers? Evidence from China - Pan, Lan; Li, Gang; Wan, Haoran (Frontiers in Public Health, 2024)
Background: Transforming rural migrant workers’ consumption potential into a consumption booster requires ensuring their equal rights as urban residents. The adequate access to Basic Public Health Services (BPHS) help effectively tackle rural migrant workers’ health challenges and promote the well-being of this vulnerable population. Assessing the welfare effects of BPHS through a consumption perspective offers valuable insights and provides policy implications for enhancing the equity of BPHS and achieving common prosperity. Methods: Utilizing the household-level data from China Migrants Dynamic Survey 2017 (CMDS 2017), this study comprehensively evaluated the effects of BPHS on rural migrant workers’ household consumption by combining the methods of OLS, PSM and IV. Results: The enhancement of BPHS promotes rural migrant workers’ household consumption even after considering endogeneity problems. Mechanism analysis indicates that BPHS imposes its positive effects on rural migrant workers through improving health literacy and increasing citizenization willingness. Furthermore, we identified heterogeneous effects across individual and household characteristics of rural migrant workers, and their flow patterns. Conclusions: Our analysis indicates that BPHS plays a greater role in promoting household consumption of socially vulnerable groups, such as trans-provincial migration, rural migrant workers in old generations, and with lower-level income. Overall, these results suggest that the welfare effects of BPHS are inclusive in China.